Sorption of copper by dye-treated oil-palm fibres - Low, K.S.; Lee, C.K.; Lee, K.P. (Elsevier Science Publishers, 1993)
Both dye-treated and natural oil-palm fibres from a palm-oil mill were used to remove copper and related heavy metal cations from solutions. The sorption of copper for both types of fibres was studied under various conditions, the parameters being effect of pH, initial concentrations, presence of other metal cations and chelators. The results showed that dye coating had a pronounced effect on metal sorption. A comparative study on the uptake by the fibres of metal cations from electroplating wastes was also undertaken.